Noncompetes as Tax Evasion - Rebecca N. Morrow (Washington University Law Review, 2018)
Al Capone famously boasted of his criminal empire: “Some call it bootlegging. Some call it racketeering. I call it a business.” Treasury Agent Frank Wilson and Prosecutor George Johnson put Capone behind bars not by disputing his characterization and pursuing murder or assault or RICO charges, but by accepting it and enforcing its tax implications. Irrespective of their legality, Capone’s businesses were profitable, and Capone had not reported their profits for tax purposes. A simple application of bedrock tax law achieved what other legal routes failed to achieve and sent Capone to Alcatraz. The trick was to see the tax argument. Policymakers should use a similar approach to curtail the excessive, exploitative, and anticompetitive use of employment noncompete agreements. Currently, nearly one in five (or thirty million) American workers is bound by an employment noncompete. Employers claim that they adequately compensate employees for noncompete restrictions with higher wages, bigger raises, and/or more generous bonuses. Policymakers scoff at this claim and use contract law to attack them. Unfortunately, employment noncompetes are like Al Capone in that they have flourished despite the law’s efforts to restrain them. Recently, the largest study of noncompetes in U.S. history paradoxically found that their prevalence is unaffected by their enforceability. In states like California that refuse to enforce employment noncompetes, they are as common as in states that uphold them. Contract law has proved ill-equipped to respond to the pervasive, expanding, and damaging use of noncompetes. This Article is the first to shift the focus and to argue that employment noncompetes, as employers currently use them, constitute tax evasion and should be attacked as such. If employers pay employees for noncompetes through compensation, then by employers’ own account, this compensation is not purely an expense associated with immediate benefits; rather, it is an expenditure associated with future benefits—benefits that the employer will enjoy years after payment. Thus, the IRS should stop allowing employers to fully immediately deduct the compensation they pay to employees subject to noncompetes and instead should require that an adequate portion of total compensation be allocated to the noncompete and amortized over the restricted period, beginning when employment ends.
Keywords: employment law; employment noncompete agreements; noncompete; tax evasion; compensation; negative growth; private enforcement; expense; expenditure; employer behavior; employer-funded information; contract law; tax law; post-employment mobility; amortization; anti-competitive contracts; at-will employment; long-term expenditure; IRS; internal revenue service; capitalization